Aceh Cultural Asset Data Management System Using Website-Based Business Process Reengineering Method - Kairul Abdi; Samsudin (Universitas Budi Darma, 2026)
This study aims to design and implement a cultural asset data management system in Aceh using a website-based Business Process Reengineering (BPR) approach. Aceh possesses abundant cultural assets with significant historical, traditional, and artistic value; however, their management has been constrained by manual, fragmented, and inefficient processes, resulting in difficulties in data monitoring, maintenance scheduling, and information dissemination. To address these challenges, this research applies the BPR method to analyze and redesign existing workflows, followed by the development of an integrated web-based management system. The proposed system features a user-friendly interface that enables administrators and stakeholders to manage asset records, update asset conditions, perform data searches, monitor preservation status, and generate reports efficiently. The novelty of this study lies in the integration of BPR methodology with a web-based cultural asset management platform specifically tailored to Aceh’s cultural preservation needs, combining workflow optimization, centralized data storage, and real-time monitoring within a single system. Unlike previous studies that mainly focus on digitization or database development, this research emphasizes comprehensive business process transformation to improve operational efficiency and governance quality. System evaluation was conducted through functionality testing, usability assessment, and efficiency analysis. The results show that the implementation of the proposed system reduced average data processing time by 68%, improved data retrieval speed by 74%, and increased data accuracy and consistency from 71% to 94% compared to the previous manual system. In addition, usability testing involving 30 respondents achieved a System Usability Scale (SUS) score of 86.5, indicating excellent user acceptance and system effectiveness. These findings demonstrate that the application of BPR significantly enhances cultural asset management performance while supporting more sustainable preservation and decision-making processes. This study is expected to serve as a reference for other regions seeking to implement information technology solutions for cultural heritage preservation and management.